THE ADIWIYATA PROGRAM IN FORMING ENVIRONMENTAL CHARACTER IN ELEMENTARY SCHOOL STUDENTS - Mushodikul Umam; Endang Poerwanti; Budiono Budiono (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
Environmental issues have become one of the most pressing global challenges, requiring serious attention from various sectors, including the field of education. Instilling environmental awareness and fostering a love for the environment from an early age is a strategic step toward developing a generation that is both environmentally conscious and responsible for environmental sustainability. In this context, the Adiwiyata Program serves as an initiative aimed at creating environmentally friendly and cultured schools. The background of this study is rooted in the importance of early environmental education in shaping sustainable awareness and environmentally conscious behavior. This study aims to explore: 1) How the Adiwiyata Program contributes to the development of students' environmental character at SD Muhammadiyah 4 Malang; and 2) How the status of a nationally recognized Adiwiyata school impacts students' environmental mindset and character development. This research employs a qualitative method with a descriptive approach. Data were collected through semi-structured interviews, field observations, and documentation. The informants consisted of the school principal, teachers, students, and parents. The findings reveal that the Adiwiyata Program at SD Muhammadiyah 4 Kota Malang has successfully fostered environmental character among students through various activities organized by several working groups (Pokja). These activities include routine waste management practices, plant maintenance, energy conservation, and regular cleaning efforts, all of which are integrated into the learning process. Environmental conservation values have been instilled independently, as evidenced by students' sense of responsibility, care, and active participation in maintaining cleanliness and the natural aesthetics of both their school and home environments.